Hairy root culture: a potent method for improved secondary metabolite production of Solanaceous plants - Biswas, Diptesh; Chakraborty, Avijit; Mukherjee, Swapna; Ghosh, Biswajit (Frontiers in Plant Science, 2023)
Secondary metabolites synthesized by the solanaceous plants are of major therapeutic and pharmaceutical importance, many of which are commonly obtained from the roots of these plants. 'Hairy roots', mirroring the same phytochemical pattern of the corresponding root of the parent plant with higher growth rate and productivity, are therefore extensively studied as an effective alternative for the in vitro production of these metabolites. Hairy roots are the transformed roots, generated from the infection site of the wounded plants with Agrobacterium rhizogenes. With their fast growth, being free from pathogen and herbicide contamination, genetic stability, and autotrophic nature for plant hormones, hairy roots are considered as useful bioproduction systems for specialized metabolites. Lately, several elicitation methods have been employed to enhance the accumulation of these compounds in the hairy root cultures for both small and large-scale production. Nevertheless, in the latter case, the cultivation of hairy roots in bioreactors should still be optimized. Hairy roots can also be utilised for metabolic engineering of the regulatory genes in the metabolic pathways leading to enhanced production of metabolites. The present study summarizes the updated and modern biotechnological aspects for enhanced production of secondary metabolites in the hairy root cultures of the plants of Solanaceae and their respective importance.